Cultural stress and psychological symptoms in recent Venezuelan immigrants to the United States and Colombia. (November 2018) - Schwartz, Seth J.; Salas-Wright, Christopher P.; Pérez-Gómez, Augusto; Mejía-Trujillo, Juliana; Brown, Eric C.; Montero-Zamora, Pablo; Meca, Alan; Scaramutti, Carolina; Soares, Mary H.; Vos, Saskia R.; Javakhishvili, Nino; Dickson-Gomez, Julia
Abstract: Background: The present study was designed to compare cultural stressors, psychological distress, and their interrelationships between recent Venezuelan immigrants in the United States and in Colombia. Cultural stress theory suggests that immigrant groups in receiving contexts that are more culturally similar to them would report less discrimination, and a less negative context of reception, compared to immigrant groups settling in countries that are more culturally dissimilar. We therefore hypothesized that recent Venezuelan immigrants in Colombia would report less cultural stress, and less psychological distress (depressive and anxiety symptoms), compared to recent Venezuelan immigrants in the US. Method: A sample of 647 Venezuelan immigrants (78% had migrated within one year prior to assessment) completed surveys assessing perceived discrimination, negative context of reception, depressive symptoms, and anxiety symptoms. Results: Contrary to expectations, Venezuelan immigrants in Colombia reported significantly ( p  < .05) greater discrimination, a worse context of reception, and more depressive symptoms, compared to their counterparts in the US. Mediational models indicated that a negative context of reception was related to depressive and anxiety symptoms indirectly through experiences of discrimination. Conclusion: The mean differences contradict what cultural stress theory would predict, and suggest that mechanisms other than cultural similarity and dissimilarity may be responsible for the observed differences. However, the structural relationships among these factors are consistent with theory.